Central and Provinsional Authorities’ Tussles In Cross Border Palm Oil Plantation Ventures in Indonesia: Experiences of Malaysian Multinational Enterprises (MNEs) - Nuarrual Hilal Md Dahlan; Yusramizza Md Isa@Yusuff; Al-Hanisham Mohd Khalid (International Journal of Supply Chain Management, 2018)
Conflict between the Central and Provincial Governments in Indonesia is one of the main hindrances for Malaysian MNEs implementing palm oil investment in Indonesia. This issue if not resolved can lead to the failure of the MNEs investment and affect FDI flows. The objective of this paper is to discuss the issues arising from conflict between the Central and Provincial Governments in Indonesia faced by the Malaysian MNEs in Indonesia. This paper provides the approaches that have been taken to address the problems. Qualitative and legal research methodologies were used in this paper. From this writing, certain data can be generated to show the severity and gravity of the problems arising from land conflict in palm oil plantation ventures in Indonesia and the approaches that have been taken to deal with the problems. The findings of the research will benefit the Malaysian MNEs in its internationalization of palm oil plantation ventures.